Ultraviolet-C-based sanitization is a cost-effective option for hospitals to manage health care-associated infection risks from high touch mobile phones - Cook, David C.; Olsen, Matthew; Tronstad, Oystein; Fraser, John F.; Goldsworthy, Adrian; Alghafri, Rashed; McKirdy, Simon J.; Tajouri, Lotti (Frontiers in Health Services, 2025)
Mobile phones have become essential tools for health care workers around the world, but as high touch surfaces, they can harbor microorganisms that pose infection risks to patients and staff. As their use in hospitals increases, hospital managers must introduce measures to sanitize mobile phones and reduce risks of health care-associated infections. But such measures can involve substantial costs. Our objective in this paper was to consider two mobile phone risk mitigation strategies that managers of a hypothetical hospital could implement and determine which involves the lowest cost. The first strategy required all staff to sanitize their hands after every contact with a mobile phone. The second involved the hospital investing in ultraviolet-C-based mobile phone sanitization devices that allowed staff to decontaminate their mobile phones after every use. We assessed each intervention on material and opportunity costs assuming both achieved an equivalent reduction in microbe transmission within the hospital. We found that ultraviolet-C devices were the most cost-effective intervention, with median costs of approximately AUD360 per bed per year compared to AUD965 using hand hygiene protocols. Our results imply that a 200-bed hospital could potentially save AUD1–1.4 million over 10 years by investing in germicidal ultraviolet-C phone sanitizers rather than relying solely on hand hygiene protocols.